Pelaksanaan Kurikulum PAUD Berbasis Karakter dalam Pembentukan Kebiasaan Sholat Anak Usia Dini di TK ABA Kartini Cabang Binjai Kota - Fitri, Halimah; Chairanda, Mutiara; Khodijah, Nurul; Rozana, Salma; Susanti, Sri (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
This study investigates the implementation of a character-based early childhood education (ECE) curriculum in fostering prayer habits among young children at TK ABA Kartini, Binjai City Branch. Employing a qualitative ethnographic approach, the research involved 25 kindergarten B students, utilizing observation, interviews, and documentation for data collection. Findings indicate that the cultivation of religious character—particularly discipline in worship—is facilitated by systematic habituation and consistent teacher role-modeling during daily routines, such as ablution and congregational duha prayers. Teachers serve as exemplars in project-based learning, integrating religious values into thematic activities. The adoption of deep learning strategies enables students to move beyond imitation, promoting reflective understanding and internalization of positive behaviors. Notable behavioral changes include increased independence, responsibility, and regularity in performing prayers, both at school and at home. These results underscore the pivotal function of teachers as role models in nurturing religious character from early childhood through holistic and contextual educational practices.